Two new species of Cypretta Vávra, 1895 (Crustacea, Ostracoda) from Thailand and discussion of genus - Savatenalinton, Sukonthip (Zootaxa, 2018)
Two Cypretta species from Thailand are described: Cypretta aculeata n. sp. and Cypretta triangulata n. sp. Cypretta        aculeata n. sp. can be characterized chiefly by the valve surface equipped with long setae, spine-like bristle and distinctive pits, the presence of tubercles on postero-ventral margin of the internal left valve and the denticulated ridge on the postero-ventral part of the internal right valve, the long d1 seta on the second thoracopod (T2), and the long Sp seta on the caudal ramus (CR). Based on the valve surface ornamentation, C. aculeata n. sp. is similar to C. globosa (Brady, 1886), C.            intonsa Furtos, 1936, C. spinosa Cohuo-Durán et al., 2013 and C. vivacis Würdig & Pinto 1993. A key to the species within this group is thus provided. The main diagnostic features of Cypretta triangulata n. sp. are the triangular carapace in the dorsal view, the absence of tubercles on the postero-ventral margin of the internal left valve, the presence of denticulated ridge on the postero-ventral part of the internal right valve, the short d1 seta on T2 and the long Sp seta on the CR. The diagnostic characters for the species identification of the genus Cypretta are briefly discussed with regard to the morphology and number of the septa and lunules, the traits of the internal side of the valves, the features of soft body parts (such as the mandible, the thoracopods and the CR) and the morphological aspects of the hemipenis.